Flight Aerodynamic Performance of Single and Twin Air Channel for Radar Cross Section Reduction - Ranjan, Shivani; Yadav, Manish Varun (2023 3rd International Conference on Range Technology (ICORT), 2023)
For at least four decades, scientists have been working on Radar Absorbing Materials (RAMs). The effectiveness of a system has been the primary criterion for evaluating military aircraft. The designer's objective is thus to optimise the efficiency of the system. Presented article describes a preliminary study of employing Radar Absorbing Shield (RAS) to reduce Radar Cross Section (RCS) on air channels. To begin, a three-dimensional model of a single and twin air channel has been generated through using the software "Computer Aided Three-Dimensional Interactive Application" (CATIA) for numerical computation. Following that, the possible applications of Radar absorbing shield (RAS) on the surface of the both air channel were assessed in order to lower their Radar Cross Section (RCS). The outcomes were then evaluated to see the feasibility of Radar absorbing shield (RAS).